Exploration of Research Hotspots in Technology-Enabled Oral English Teaching in China (2010-2025): Based on CiteSpace - Xi Chen; Weijie Hu (Yayasan Visi Intan Permata, 2025)
Against the backdrop of advancing educational digitization, the auxiliary role of digital technology in oral English teaching has become increasingly prominent. As a global topic within the field of Computer-Assisted Language Learning (CALL), technology-enabled oral instruction manifests diverse pathways across different national contexts. This study employs CiteSpace 6.3.R1 software to conduct a visualization analysis of relevant journal articles indexed in China National Knowledge Infrastructure (CNKI) from 2010 to 2025. The aim is to explore research hotspots and evolutionary trends in technology-enabled oral English teaching within China. Results indicate a generally growing research interest in this field, with hotspots concentrated on the application of technologies such as artificial intelligence in higher education. However, the research still faces challenges: empirical studies remain overly concentrated on higher education in terms of breadth, while in depth they mostly focus on verifying short-term effects, lacking in-depth examination of long-term impacts and ethical dimensions. By mapping China's research landscape, this study aims to provide a differentiated case reference for global research in this field. Future research should deepen toward a systematic approach characterized by multi-contextual, long-term, and deeply integrated approaches to build a more mature smart education ecosystem.